The effect of mortgage securitization on foreclosure and modification - Kruger, Samuel (Journal of Financial Economics, 2018)
Did securitization exacerbate the foreclosure crisis by altering mortgage servicing practices? I exploit the unanticipated freeze of private mortgage securitization in 2007 to provide new evidence that securitization increases foreclosure probability and decreases modification probability. These effects are economically large and persist over time even after implementation of the Home Affordable Modification Program (HAMP) in 2009. Using hand-collected data on the contractual terms of servicing agreements, I show that servicers typically have broad discretion to modify loans but face significant incentives favoring foreclosure. The evidence implies that securitization significantly increased foreclosure rates during and after the crisis.